Macroraptorial sperm whales (Cetacea, Odontoceti, Physeteroidea) from the Miocene of Peru - Lambert, Olivier; Bianucci, Giovanni; de Muizon, Christian (Zoological Journal of the Linnean Society, 2017)
International audience The three extant sperm whale species, the giant Physeter macrocephalus and the diminutive Kogia species, are relict members of the superfamily Physeteroidea, whose evolutionary history is traced back to the late Oligocene. Although well‐preserved and diagnostic cranial remains are relatively scarce, the physeteroid fossil record reveals a considerable degree of morphological disparity (especially during the Miocene), suggesting that sperm whales occupied a broader range of ecological niches in the past. Here, we provide detailed descriptions and a (re)analysis of several new and established middle–late Miocene stem physeteroids from the Pisco Formation of southern Peru. In particular, we (1) further describe the holotype of Acrophyseter deinodon from the latest Tortonian–Messinian of Sud‐Sacaco, with new information on previously unpublished portions of the skull (including the ear bones) and a discussion of its masticatory musculature; (2) diagnose a new species of Acrophyseter, A. robustus sp. nov., based on a finely preserved skull with some associated cranial remains from the late Serravallian–Tortonian (> 9.2 Ma) of Cerro la Bruja; (3) provisionally refer a skull from Cerro los Quesos, which has been radiometrically dated to the Messinian (6.9–6.7 Ma), to Acrophyseter sp.; and (4) further describe the skull of the giant raptorial sperm whale Livyatan melvillei from Cerro Colorado, recently re‐dated to the Tortonian (9.9–8.9 Ma) based on the associated diatom fauna and Ar/Ar dating. A phylogenetic analysis based on 53 characters and 21 physeteroid species confirms the monophyly of Acrophyseter and groups this genus with the larger, middle to late Miocene macroraptorial stem physeteroids Brygmophyseter and Zygophyseter. With its unique supracranial basin morphology, Livyatan forms a separate, more crownward stem physeteroid lineage. Combined with biostratigraphic information, our cladistic hypothesis allows us to discuss the time of origin of the main physeteroid clades, as well as ...